Pembentukan Karakter Religius Siswa Melalui Program Pembiasaan Keagamaan - Aliyah Siti Azizah; Helmi Aziz (Jurnal Riset Pendidikan Agama Islam, 2025)
Abstract. This study examines the formation of students’ religious character through the religious‐habituation program at SMAN 9 Bandung. A descriptive qualitative approach was adopted to explore the phenomenon in its natural setting. Primary data were collected via classroom and campus observations, in‐depth interviews with Islamic‐education teachers and the principal, and supporting documents. Findings reveal that since 2016 the school has institutionalised a set of religious routines including congregational Dhuha prayer, daily recitation of the 99 Names of Allah, short student sermons (kultum), weekly Qur’an completion, and girls’ Islamic study circles—as part of its school culture. The program significantly enhances students’ worship discipline, sense of responsibility, social empathy, and spiritual awareness; success indicators are visible in consistent daily worship and positive behavioural changes at school and home. Key enabling factors include strong leadership commitment, teacher role‐modelling, and whole‐school collaboration, while constraints arise from uneven intrinsic motivation, varying family support, an academically heavy timetable, and limited worship facilities. Overall, the habituation program is effective in cultivating religious character, though sustained evaluation and improved infrastructural support are essential to maximise its long‐term impact. Abstrak. Penelitian ini berfokus pada pembentukan karakter religius siswa melalui program pembiasaan keagamaan di SMAN 9 Bandung. Pendekatan yang digunakan adalah kualitatif deskriptif dipilih agar peneliti dapat memahami fenomena secara mendalam dalam konteks alamiah. Data primer dikumpulkan melalui observasi, wawancara mendalam dengan guru PAI dan kepala sekolah, serta studi dokumentasi sebagai pendukung. Hasil penelitian menunjukkan bahwa program pembiasaan keagamaan, yang meliputi shalat Dhuha berjamaah, pembacaan Asmaul Husna, kultum, khotmil Qur’an, dan keputrian, terintegrasi dalam budaya sekolah sejak 2016 dan terlaksana secara terstruktur. Program ini berhasil meningkatkan disiplin ibadah, rasa tanggung jawab, empati sosial, serta kesadaran spiritual siswa; indikator keberhasilan terlihat pada konsistensi ibadah harian dan perubahan sikap positif dalam interaksi di sekolah maupun di rumah. Faktor pendukung utama mencakup komitmen pimpinan, teladan guru, dan sinergi antarwarga sekolah, sedangkan hambatan muncul dari motivasi intrinsik siswa yang belum merata, dukungan keluarga yang variatif, padatnya kurikulum, serta keterbatasan fasilitas ibadah Secara keseluruhan, program ini efektif dalam membentuk karakter religius siswa, namun keberlanjutan dan perluasan fasilitas menjadi kunci untuk memaksimalkan dampaknya.